PENERAPAN PEMBELAJARAN INKUIRI PADA MATERI KENAMPAKAN PERMUKAAN BUMI UNTUK MENINGKATKAN HASIL BELAJAR SISWA (Penelitian Tindakan Kelas pada Materi Kenampakan Permukaan Bumi Kelas III-A SDN Sindangraja Kecamatan Sumedang Utara Kabupaten Sumedang) - Tresnayani, Amelyandini; Gusrayani, Diah; Jayadinata, Asep Kurnia (Jurnal Pena Ilmiah, 2017)
Based on preliminary observations conducted on grade 3 students of a sindangraja state primary school obtained a problem, that is on the learning. The method used in this study is a classroom action research with references to the spiral model of kemmis and taggart. The subjek of this research is at grade 3 a sindarngraja state primary school as many as 24 students this research is done 3 cycles because the target of research is reached in cycle 3. As for the target that is for determined is 85% for students learning result, while for 90% for students’s activities and teacher’s performance. The data obtained in research process, that is, the teacer’s performance. Earned in 77% in cycle 1, 91% in cycle 2, and 95% in cycle 3. While the students’s activities  ot cycle 1 65%, on cycle 2 80%, and 95% in cycle 3. Learning outcomes at cycle 1 48%, on ccle 2 79%, and on cycle 3 87.5% . based on the data obtained in the research process, there has been an increase in student learning outcomes. It proves that the application of inquiry learning model can improve students learning outcomes.